Extended Versus Standard Antibiotic Course Duration in Children <5 Years of Age Hospitalized With Community-acquired Pneumonia in High-risk Settings: Four-week Outcomes of a Multicenter, Double-blind, Parallel, Superiority Randomized Controlled Trial. Issue 7 (7th June 2022) - McCallum, Gabrielle B.; Fong, Siew M.; Grimwood, Keith; Nathan, Anna M.; Byrnes, Catherine A.; Ooi, Mong H.; Nachiappan, Nachal; Saari, Noorazlina; Morris, Peter S.; Yeo, Tsin W.; Ware, Robert S.; Elogius, Blueren W.; et al.
Abstract : Background: High-level evidence is limited for antibiotic duration in children hospitalized with community-acquired pneumonia (CAP) from First Nations and other at-risk populations of chronic respiratory disorders. As part of a larger study, we determined whether an extended antibiotic course is superior to a standard course for achieving clinical cure at 4 weeks in children 3 months to ≤5 years old hospitalized with CAP. Methods: In our multinational (Australia, New Zealand, Malaysia), double-blind, superiority randomized controlled trial, children hospitalized with uncomplicated, radiographic-confirmed, CAP received 1–3 days of intravenous antibiotics followed by 3 days of oral amoxicillin-clavulanate (80 mg/kg, amoxicillin component, divided twice daily) and then randomized to extended (13–14 days duration) or standard (5–6 days) antibiotics. The primary outcome was clinical cure (complete resolution of respiratory symptoms/signs) 4 weeks postenrollment. Secondary outcomes included adverse events, nasopharyngeal bacterial pathogens and antimicrobial resistance at 4 weeks. Results: Of 372 children enrolled, 324 fulfilled the inclusion criteria and were randomized. Using intention-to-treat analysis, between-group clinical cure rates were similar (extended course: n = 127/163, 77.9%; standard course: n = 131/161, 81.3%; relative risk = 0.96, 95% confidence interval = 0.86–1.07). There were no significant between-group differences for adverse events (extended course: n = 43/163, 26.4%; standard course, n = 32/161, 19.9%) or nasopharyngeal carriage of Streptococcus pneumoniae, Haemophilus influenzae, Moraxella catarrhalis and Staphylococcus aureus or antimicrobial resistance. Conclusions: Among children hospitalized with pneumonia and at-risk of chronic respiratory illnesses, an extended antibiotic course was not superior to a standard course at achieving clinical cure at 4 weeks. Additional research will identify if an extended course provides longer-term benefits.